2011
DOI: 10.1097/pec.0b013e3182307a4b
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Recognition of Elevated Triage Blood Pressure in the Pediatric Emergency Department

Abstract: In this study, more than half of the patients had elevated triage BP (≥ 90th percentile), which was rarely recognized by emergency department practitioners regardless of specialty or experience. Early recognition of elevated triage BP offers opportunities for diagnosis of hypertension and related disorders but is challenging to accomplish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…We have previously shown that only 13% of elevated BPs measured in an urban academic pediatric primary care setting were recognized as elevated by providers. 4 These results are similar to those obtained in a pediatric emergency department setting 5 and in a large pediatric primary care setting. 6,7 …”
Section: Introductionsupporting
confidence: 80%
“…We have previously shown that only 13% of elevated BPs measured in an urban academic pediatric primary care setting were recognized as elevated by providers. 4 These results are similar to those obtained in a pediatric emergency department setting 5 and in a large pediatric primary care setting. 6,7 …”
Section: Introductionsupporting
confidence: 80%
“…Several studies have documented a systematic underrecognition of pediatric hypertension, even when blood pressure is measured. [35][36][37] The high frequency (89%) of height measurement in patients whose blood pressure was measured suggests that screening could have occurred at most preventive visits. However, in at least 11% of preventive visits in which blood pressure was measured, blood pressure values could not have been interpreted appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, hypotension is a late sign of shock in children and, on the other hand, the triage of children with hypertension in the emergency department may result in high prevalence of false positives 24. Other triage tools, such as MTS,8 Paed CTAS,7 ESI-4,6 and ATS,19 do not include mandatory measurement of blood pressure, but only the initial assessment of clinical signs of shock, such as thin pulses, delayed capillary refill, sweating, and pallor.…”
Section: Discussionmentioning
confidence: 99%